Osteogenic potential of murine periosteum for critical-size cranial defects - Ruvalcaba-Paredes, E.K.; Hidalgo-Bastida, L.A.; Sesman-Bernal, A.L.; Garciadiego-Cazares, D.; Pérez-Dosal, M.R.; Martínez-López, V.; Vargas-Sandoval, B.; Pichardo-Bahena, R.; Ibarra, C.; Velasquillo, C. (British journal of oral & maxillofacial surgery, 2016)
Tissue engineering of bone has combined bespoke scaffolds and osteoinductive factors to maintain functional osteoprogenitor cells, and the periosteum has been confirmed as a satisfactory source of osteoblasts. Suitable matrices have been identified that support cell proliferation and differentiation, including demineralised bone matrix (both compatible and osteoinductive) and acellular human dermis. We have evaluated the osteogenic potential of an osteogenic unit, developed by combining periosteum, demineralised bone matrix, and acellular human dermis, in rodents with critical-size cranial defects. Briefly, remnants from the superior maxillary periosteum were used to harvest cells, which were characterised by flow cytometry and reverse retrotranscriptase-polymerase chain reaction (RT-PCR). Cells were cultured into the osteogenic unit and assessed for viability before being implanted into 3 rodents, These were compared with the control group (n=3) after three months. Histological analyses were made after staining with haematoxylin and eosin and Von Kossa, and immunostaining, and confirmed viable cells that stained for CD90, CD73, CD166, runt-related transcription factor, osteopontin, and collagen type I in the experimental group, while in the control group there was only connective tissue on the edges of the bone in the injury zone. We conclude that osteogenic unit constructs have the osteogenic and regenerative potential for use in engineering bone tissue.